Marketing in the Metaverse: Exploring marketing opportunities and potential pitfalls - Stefanie Wannow; Chiara Beck (PraxisWISSEN Marketing, 2023)
Companies from diverse industries, such as gaming, travel, and retail, have started to explore emerging marketing opportunities in the Metaverse. However, there is great uncertainty regarding effective strategies in this new "world". As research is still in its infancy, we aim to contribute to a better understanding of Metaverse marketing and its opportunities and challenges. Interviews with experts from different industries highlight the Metaverse's potential for more personalized and immersive marketing strategies. Community-building, but also innovative Metaverse products, such as NFTs, are seen as particularly promising. However, a prerequisite for successful Metaverse marketing is the creation of a safe environment and sufficient technological expertise. – – Unternehmen aus verschiedenen Branchen wie Gaming, Reisen und Einzelhandel erkunden derzeit, welche Marketingpotenziale das Metaverse bietet. Es besteht jedoch noch große Unsicherheit über effektive Strategien in dieser neuen "Welt". Da die Forschung noch am Anfang steht, möchten wir zu einem besseren Verständnis des Metaverse-Marketings und seiner Chancen und Herausforderungen beitragen. Interviews mit Experten aus verschiedenen Branchen zeigen das Potenzial des Metaverse für personalisierte und immersive Marketingstrategien. Die Entwicklung von Communities, sowie innovative Metaverse-Produkte, wie z.B. NFTs, werden als besonders vielversprechend angesehen. Voraussetzung für ein erfolgreiches Metaverse-Marketing sind jedoch ein sicheres Umfeld und ausreichend technologisches Know-how.
Keywords: 650; Metaverse; virtual reality; marketing; user experience; digital transformation